Single nucleotide polymorphism (SNP) of Jatropha curcas associated with the content of phorbol ester - Vega Quirós, Natasha (2021)
Jatropha curcas is an oleaginous plant of multiple uses including the production of biodiesel. By-products after oil extraction can be used for animal feed, but the presence of toxic compounds such as phorbol esters limits its use. The availability of non-toxic germplasm permits the generation of varieties free of phorbol esters. In the present study, we validated SNP markers associated with the absence or low content of phorbol esters in fifty-four accessions from nine different countries conserved in a germplasm bank of J. curcas in Costa Rica. Accessions from Mexico, where non-toxic germplasm occurs naturally, were included. The identification of toxic germplasm with levels of PE > 0.1 mg/g was possible with four SNPs (SNP22, SNP24, SNP25772 and SNP25886). Besides, the discrimination of accessions of Mexico from other countries was possible with both a unique haplotype of three SNPs (SNP22, SNP24 and SNP25772) and two genotypes of SNP25886. Only the genotype T/T of SNP25886 was exclusively associated with non-toxic accessions. The genotype C/T of SNP25886 was associated with accessions of Mexico with variable content of PE (from 0 to 0.4148 mg/g) which may serve as a first line of screening to find potencial non-toxic plants. The SNPs validated in this work, in combination with the quantification of PE by HPLC, may serve to select non-toxic germplasm in plant breeding programs that pursue the development of non-toxic varieties of J. curcas.